Reactivity of Digestive Mucins in freshwater Snail Bellamya bengalensis (l) Against Copper sulphate Induction - Kamble, N A; Kamble, S B (Asian Journal of Biological and Life Sciences, 2012)
Freshwater snail Bellamya bengalensis was used for the toxicological study against copper sulphate in pre-determined LC50 concentrations (0.56ppm) up to 96 hrs. Histopathology was investigated by using standard H-E (Hematoxylene-Eosine) staining technique. Cellular damage was found in midgut (stomach cells) mucus cells, epithelial lining and typhosolar cells. Depleted mucin was found in PAS and Alcian blue (AB) staining technique. Highly reactive proteioglycans was found in mucus secretary cells. Histopathology and chemical changes were comparatively discussed in relation to digestive mechanism of experimental animals.